“Aqui cada um faz o seu rolê”: práticas organizativas dos blocos de rua afro do carnaval de Belo Horizonte - Ana Flávia Rezende (2022)
Carnival procession groups of Afro Street in Belo Horizonte, Angloa Janga and Magia which developed from collective resistance projects, call our attention to the political dimension of these organizations. This study, therefore, aims to understand how the dynamics of the organizational practices in the afro street carnival procession groups in Belo Horizonte, Angola Janga and Magia Negra, make possible the achievement of the political dimension of these organizations in the perspective of social change as well as ethnic-racial valorization. From questioning “how the organizational practices of the Afro street procession groups in the city of Belo Horizonte relate to an ethnic-racial valorization project?” I looked into ethnography to access the Afro procession groups Angola Janga and Magia Negra in full operation, in order to understand how people instantiate their practices in the here and now, it was necessary to immerse myself into the field of investigation. In order to reach the complexity within the afro organization, I started my journey from the object, thus, I hereby present the afro street procession groups of the city of Belo Horizonte with an emphasis on the history of the Angola Janga and Magia Negra procession groups. As Afro procession groups in Brazil cannot be talked about without giving reference to the pioneers, after acknowledging the pioneers, I turned to the Bahian carnival and the Afro procession groups there to better understand how this type of organization arises, thus, in what social context or racial relations it takes place. Despite the significant influences of the pioneering Afro procession groups, this research focuses on the city of Belo Horizonte, which has some specificities that influenced or is influencing the emergence of street carnival groups, as well as the rebirth of the city's street carnival. In this context, I delved deeper into the relationship between the city of Belo Horizonte and Carnival, which helped to better understand the organizational processes of the Afro street procession groups of Angola Janga and Magia Negra. With immersion into the field, I realized it is possible to access the practices of these groups from the organizational processes that take place in three major phases, they are: the mobilization / preparation of the procession, presentation / procession and the closing / post-procession which are cyclically related and in which each practice adopted at a given phase interferes with the next phase and consequently in the existence and perpetuation of the Afro procession groups studied. The main research findings show that the practices of Angola Janga and Magia Negra procession groups present themselves as a resistant group which demonstrates, constituting an effective instrument for combating social disorder and the ability of ensuring change. In addition, collectivity and consequently the construction of alliances between marginalized subjects must be considered an important organizational principle for black organizations.